Patriotism - Johnson L.C.; The Rosen Publishing Group, Inc (New York: The Rosen Publishing Group, Inc, 1990)
Examines the concept of patriotism, discussing its many forms, symbols, and meanings.
Junior Non-Fiction-: Juvenile Literature